Expression of bap gene in multidrug-resistant and biofilm-producing Acinetobacter baumannii clinical isolates - Maedeh Kakavan; Mehrdad Gholami; Mohammad Ahanjan; Mohammad Ali Ebrahimzadeh; Maryam Salehian; Fatemeh Roozbahani; Hamid Reza Goli (BMC Microbiology)
Abstract Introduction Acinetobacter baumannii is a significant biofilm-producer and antibiotic-resistant pathogen associated with various infections caused in humans. This study aimed to investigate the expression level of the bap gene in multidrug-resistant and biofilm-producer clinical isolates of A. baumannii. Materials and methods One Hundred A. baumannii clinical isolates were collected from hospitalized patients and identified by phenotypic and genotypic tests. The antibiotic resistance pattern of the isolates was determined by the disk agar diffusion method. The ability of biofilm production was investigated using the microtiter plate test. This study employed the Real-time PCR method to evaluate the expression level of the bap gene. Results Ninety nine percent A. baumannii isolates were MDR. However, the highest resistance rate was observed against ciprofloxacin (100%), while ceftazidime was the most effective drug. Also, 49%, 49%, and 2% of the isolates were strong, moderate, and weak biofilm-producing, respectively. However, we detected no strain without the ability to produce biofilm. Most strong and moderate biofilm-former isolates were non-susceptible to all tested antibiotics. An increased expression level of the bap gene was detected in 99% of the isolates. The results of the present study suggest a correlation between the bap gene expression level and the development of multidrug resistance and biofilm formation in A. baumannii isolates. Conclusion This research emphasizes the importance of biofilm formation in the emergence of multidrug-resistant A. baumannii strains in healthcare settings, making them progressively difficult to control. The bap gene may be a considerable target for the development of novel anti-A. baumannii treatment option and eradication of the biofilm formation by this organism.